Czech Republic : 2019 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2019)
The economy is doing well, but supply constraints are biting. Growth has slowed as the economy has reached capacity limits, with very low unemployment even as participation has increased. Recent wage increases have been very strong, ahead of productivity. So far, inflation remains contained. The economy continues to run a current account surplus, even though domestic absorption has picked up. But the housing market is pressured, especially in metropolitan areas. Policies should balance risks of overheating against a faster-than-expected slowdown and aim to boost potential growth.